PENDAMPINGAN UMKM BATIK LASEM MELALUI INOVASI CANTING CAP DAN DIGITAL MARKETING - Azizah, Noor; Wibowo, DS. Drajad; Andriyani, Santi; Mahmudi, A. Aviv; Nasihah, Zahrotun; Najid, Muhammad Reza Ahsanun (Jurnal AbdiMas Nusa Mandiri, 2025)
UMKM Batik Tulis Lasem is one of the superior product MSMEs in Rembang Regency. The partners in this service are 2 MSMEs engaged in batik, namely Real Asto Batik and Safila Batik. The problems of both partners are the lack of product innovation and the lack of current marketing techniques. The purpose of this service is to increase partners' knowledge and skills regarding stamped batik techniques and digital marketing. In addition, the purpose of this service is to improve the management and productivity of partners in the lasem batik business. The methods in this service are socialisation, training and mentoring, technology application and evaluation. The results of the service showed that the skills and knowledge of the partners' stamping techniques and digital marketing increased with a percentage of 44% increasing very high, 54% stated high. In addition, the results of the programme evaluation also showed that the performance of the service team was very good. This programme became one of the programmes that had a positive impact on partners in particular, and in general, improving the economy and tourism of Rembang through textile and fashion products.